Berlin's Palace - Sölch, Brigitte (Architectural histories, 2021)
Berlin has experienced a recent spate of major civic construction projects. This review comprises critical assessments, by three different authors, of three of those recently completed projects: the Berlin Palace and Humboldtforum (Brigitte Sölch), the redesign of the Kulturforum (Elke Nagel), and the new Berlin-Brandenburg Airport (Max Hirsh).